BOLAJAQ OQÍTÍWSHÍLARDA ÁDEP-IKRAMLÍLÍQ KÓNLIKPELERDI JETILISTIRIWDE ETNOPEDAGOGIKALÍQ QÁDRIYATLARDÍŃ ÁHMIYETI - Pazılov, A.K. (SCIENCE and SOCIETY, 2025)
The article comparatively describes the research work, problems, and results of observation conducted on the use of ethnopedagogical values in the work of improving the moral skills of future teachers, and shows its significance.